Body Rejuvenation - Alam, Murad; Pongprutthipan, Marisa (Springer New York : Imprint: Springer, 2010)
In recent years, there has been a growing emphasis on minimally invasive procedures, which have revolutionized the safety and convenience of cosmetic surgery. Such procedures are often performed in combination with a series of minor procedures collectively providing results formerly possible only after major incisional surgery. As patients and physicians have become familiar with minimally invasive facial rejuvenation, there is growing interest in adapting techniques for use off the face. The same lasers, fillers, and other techniques that can improve the appearance of the forehead or lips are useful for the chest or hands. Of course, procedures have to be modified for use on the trunk and extremities. For instance, off the face, gentler treatment approaches can be preferable, in part because of reduced blood perfusion and slower wound healing. Body Rejuvenation is the first practical manual that describes off-the-face minimally invasive rejuvenation. Sections are organized by body area, and within each section, individual chapters contain step-by-step treatment algorithms. Chapters are brief and concise by design, so interested readers can readily obtain the information necessary to treat patients successfully. Expert authors share their experience with body rejuvenation, so that you don't have to learn by trial and error.